STUDENTS' PERCEPTION OF USING EDPUZZLE IN LISTENING ASSESSMENT - Syifa Fadhilah Hamid (English Language Education Department, Faculty of Teacher Training and Education, Syekh-Yusuf Islamic University (PBI FKIP UNIS), 2022)
Edpuzzle is a useful website for teachers to find and edit online videos whether it is from YouTube, TED Talks, or Khan Academy, etc., to present it to their students in the classroom. In addition, Edpuzzle flourished to become one of the effective tools in listening assessment because student’s progress is easily tracked by the teacher and assigned videos are graded by Edpuzzle. This is a survey study which proposed to get an empirical data about students’ perceptions of using Edpuzzle in listening assessment. The result of this study showed that students’ perceptions of using Edpuzzle in listening assessment are positive. Using video in Edpuzzle perceived as an up-to-date and interesting way to be used in listening assessment based on 90% of the respondents, and they agreed that the content of the video provided in Edpuzzle as the listening assessment media was authentic since it is related to their daily life conversation. The use of Edpuzzle in listening assessment is perceived and received positively by the students of SMK Diponegoro 1 Jakarta who have ever used Edpuzzle in their listening assessment.